MEANING OF RAMBU SOLO RITE SYMBOLS AND ITS IMPLICATIONS FOR MEMBERS OF THE TORAJA CHURCH PALAWA CONGREGATION: " AN INTERDISCIPLINARY APPROACH WITH SOCIO-DISCOURSE ANALYSIS STUDIES” - Yonathan Mangolo; A. K. Sampeasang (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Aluk is a system of life that occurs in all areas of human life that includes customs and culture. The aluk that was already in the sky, and Puang Matua and the gods were brought the provisions of the aluk. So that the relationship between in heaven and on earth is bound together. So it appears in Aluk Rambu Solo'. One of them that is still being done today is the installation of Rambu Solo rite symbols. In making and installing the Rambu Solo' symbol, there are certain conditions that must be met. The symbols of Rambu Solo' rites are rituals to remember and honor ancestors who have died and can bless and protect the family. So this is the background so that the author wants to explore the meaning of the symbols of Rambu Solo' Rite and theological studies. In this study, the author uses “socio-discourse analysis" which is an interdisciplinary approach that combines elements of social analysis and discourse analysis. This method aims to understand how language is used in a particular social context and how it reflects, creates, or reproduces social structures, powers, identities, and social relations. Here are the general steps in conducting research using the socio-discourse analysis method.The results showed that the making and installation of Rambu Solo' rite symbols is still within the understanding of Aluk Todolo and is seen as a legacy from ancestors. In the making and installation of the symbols of the Rambu Solo rite , the Gospel Crystal has actually been seen, but it is still in the understanding of Aluk Todolo. Therefore, through the creation and installation of Rambu Solo rite symbols, it is necessary to accompany and direct the Torajan people in understanding the meaning of Rambu Solo rite symbols so that they can enjoy the gospel of Christ through culture